Analysis of older adults visiting the emergency department with fever as a suspected Covid-19 vaccine-related adverse reaction: A retrospective multicenter study. Issue 8 (August 2022) - Jeong, Sikyoung; Hong, Sungyoup; Oh, Taehoon; Woo, Seon Hee; Lee, Woon Jeong; Kim, Daehee; Jeong, Won Jung
Abstract: Introduction: After COVID-19 vaccination was initiated, the number of patients visiting the emergency department (ED) with vaccine-related adverse reactions increased. We investigated the clinical features of older adults (aged 65 years and older) visiting the ED with self-reported COVID-19 postvaccination fever. Methods: We conducted a retrospective observational study at three EDs between March 2021 and September 2021. Patients who reported adverse reactions, fever (≥37.5 °C) and/or febrile sensation or rigors following COVID-19 vaccination were included. The demographic and clinical data of these patients were collected by reviewing their medical records. Results: A total of 562 patients were selected, and 396 (70.5%) were female. The older adult group included 155 (27.6%) patients, and the median age was 75 (69–79 years). The older adults less frequently had a fever (≥37.5 °C) upon ED presentation (75.5% vs. 85.7%, respectively), used more emergency medical services (43.9% vs. 18.7%, respectively), and visited an ED more frequently during early hours (00:00–06:00) (31% vs. 20.1%, respectively) compared to the younger adults (p = 0.004, p < 0.001 and p = 0.036). Fewer older adults visited an ED within 2 days of fever onset (73.5% vs. 84%) (p = 0.012), and more older adults were admitted for medical conditions other than vaccine-related adverse reactions (32.9% vs. 4.2%) (p < 0.001). Older adults received more thorough testing (laboratory and imaging tests). Among the older adults, the admission rate was associated with age (p = 0.003). Conclusion: Older adults presenting with fever as an adverse reaction following COVID-19 vaccination less frequently had a fever upon visiting the ED, required more ED testing, and had higher admission rates for non-vaccination-related medical conditions.